Consumo de drogas psicoactivas por adolescentes escolares de Assis, SP - Guimarães, José Luiz; Godinho, Pedro Henrique; Cruz, Rubens; Kappann, Jair Izaías; Tosta Júnior, Lairto Alves (FapUNIFESP (SciELO), 2004)
To quantify psychoactive drug use and investigate use-related variables among students of Assis, Brazil, a questionnaire was administered to collect sociodemographic data and identify the pattern of non-medical use of psychoactive drugs in 20% of public and private school students. The largest consumption indexes for lifetime use were seen for alcohol (68.9%) and tobacco (22.7%). Drugs most often used were: solvents (10.0%); marijuana (6.6%); benzodiazepines (3.8%); amphetamines (2.6%); cocaine (1.6%); and anticholinergics (1.0%).
Psychoactive drug use in school age adolescents, Brazil
Keywords: Adolescent; Alcohol drinking, epidemiology; Health promotion; Health surveys; Questionnaires; Smoking, epidemiology; Socioeconomic factors; Street drugs; Substance-related disorders, epidemiology; psychotropic agent; alcohol; amphetamine; benzodiazepine; cannabis; cholinergic receptor blocking agent; cocaine; solvent; addiction; adolescent; Brazil; child; drinking behavior; female; human; male; questionnaire; sex difference; smoking; socioeconomics; student; controlled study; data analysis; demography; drug use; school; social aspect; substance abuse; tobacco; Alcohol Drinking; Child; Female; Humans; Male; Psychotropic Drugs; Sex Factors; Smoking; Socioeconomic Factors; Students; Substance-Related Disorders